PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN KETERAMPILAN MENULIS NARASI SISWA KELAS IV SDN 160 PEKANBARU - Zakiah, Zakiah; Kurniaman, Otang; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTÂ The research is motivated by the lack of student skills in writing narrative with the average value of the initial data for 63.39. Formulation of the problem in this study is whether contextual learning model can improve the writing skills of narrative fourth grade students at SDN 160 Pekanbaru? This study aims to improve the skills of writing narrative fourth grade students at SDN 160 Pekanbaru through the application of contextual learning model. This research is a class act. Of this study was obtained from the students' narrative writing skills daily tests in the first cycle I mean rata70,53 or an increase of 11.26%. While the second cycle UH II increased to 80.57 and the increase of the initial data to the UH II was 21.32% . Teacher data analysis activities of the first cycle of the first meeting with the percentage of 68.7 % in both categories, the first cycle of the second meeting with a percentage of 75% with either category, the fourth meeting of the second cycle percentage is 81.25%, the second cycle of the fifth meeting of the percentage is 93.75%, whereas the activity of students in the first cycle the first meeting with the percentage of 56.25%, the first cycle of the second meeting with the percentage of 68,75%, the fourth meeting of the second cycle with a percentage of 75%, the fifth meeting of the second cycle with a percentage of 87.5%. From this research goal should be concluded that the application of contextual learning model can improve the writing skills of fourth grade students narrative SDN 160 Pekanbaru.Â Keywords: Application of Contextual Learning Model, Narrative Writing Skills